Social skills assessment of preschool children at risk for attention deficit hyperactivity disorder in Karaj, Iran - Masoumi, Shirin (2012)
The purpose of this study is to examine the relationship between demographic variables and social skills among preschool children at risk for attention deficit hyperactivity disorder (ADHD) in Karaj, Iran. The study provided research information on the relationships existing between demographic variables toward social skills among preschool children at risk for ADHD. A total of 108 respondents were selected through random sampling method to participate in this study. Respondents completed the Persian version of Teacher/Preschool of SSRS scale (Gresham & Elliott, 1990) to measure children’s social skills level. ADHDT by Gilliam (1995) and SWAN by Swanson et al. (2004) Rating Scales were used to screen children at risk for ADHD. The results of this study were analyzed using descriptive statistics, Pearson correlation and multiple linear regressions. The findings in this study showed girls have higher level of social skills subsets compared to boys. The study also found that social skills have significant and positive correlation with children’s age, parents’ education levels, family’s income level and ADHD symptoms. Results from multiple regression analysis revealed that 59.6% of preschoolers’ social skills were explained by two predictor variables, which were age and family’s income level. The relationships between demographic variables and at risk for ADHD within the context of preschoolers’ social skills were more reasonably based on the model of this study. Finally, the study argued that the early detection of preschool children’s social skills may increase the chances of early intervention of social skills among preschool children. Finally, the study suggested the role of teachers in facilitating children’s social functioning, as well as training for kindergarten and preschool teachers in Karaj, Iran.